Implementation of the ASICC learning model to improve the metacognitive students' based on lesson study extracts - Jannah, Ro'ikatul; Purwoko, Budi; Herawati, Elysabet; Primandiri, Poppy Rahmatika; Santoso, Agus Muji (JPBIO (Jurnal Pendidikan Biologi), 2024)
This research is driven by observations from the eighth-grade class at Junior High School 5 Kertosono, which revealed that lesson planning, reading comprehension, and problem-solving strategies have not been effectively utilized. Therefore, this research aims to enhance students' awareness and metacognitive skills through the application of the ASICC learning model. The focus of this study is on 18 eighth-grade students at Junior High School 5 Kertosono. This research is classroom action research based on a lesson study conducted over two cycles. The data analysis used is the scores of metacognitive awareness and skills in the first cycle compared to the second cycle, tested using N-Gain analysis. The research results reveal that metacognitive awareness in the first cycle showed that 11.1% of students were in the "medium" category, which increased to 22.2% in the second cycle. Meanwhile, metacognitive skills experienced a significant increase in the "high" category, starting from 16.7% in the first cycle and rising to 33.3% in the second cycle. The ASICC learning model can be applied to enhance students' metacognition. Another finding reveals that students with good metacognitive awareness do not always possess good metacognitive skills